Hierarchy modification induced exceptional cryogenic strength, ductility and toughness combinations in an asymmetrical-rolled heterogeneous-grained high manganese steel. (July 2022) - Zhong, Shaoxiong; Xu, Chun; Li, Yu; Li, Wei; Luo, Hao; Peng, Ruizhi; Jia, Xiaoshuai
Highlights: Effects of different heterogeneity on the tensile and impact behavior were investigated in heterogeneous-grained high manganese steels. The grain size hierarchy of HGS was modified by controlling the recrystallization growth process after AR. Strain partitioning among heterogeneous domains contributes to distinct evolutions of twins and dislocations in different HGS steels. The exceptional toughness originates from the combined effects of strong strain partitioning and crack-resistant nano-twins in the UFGs and SFGs. Abstract: The strategy of heterogeneous-structured (HGS) high manganese steels was designed by asymmetrical-rolling (AR) with annealing to obtain superior mechanical performance for cryogenic applications. The grain size hierarchy can be modified by adjusting the annealing temperature based on the growth rate of recrystallized grains. Compared with the AR-740 sample, which is dominated by a large number fraction (∼72.51%) of fine-grained (FG) zone, the AR-630 specimen consisted of larger fractions of ultrafine-grains (UFG) and sub-fine-grains (SFG) not only shows significant yield strength (YS) and ultimate tensile strength (UTS) increments to ∼983 MPa and ∼1330 MPa, respectively, but also improved tensile ductility and impact toughness value to ∼64.9% and ∼183 J‧cm −2 at liquid nitrogen temperature (LNT), respectively. The difference in YS mainly originates from the different grain boundary strengthening degrees. Moreover, the ductility enhancement can be attributed to the different evolutions of deformed substructures and strain partitioning between heterogeneous domains. On one hand, the localized stress partitioned in the UFG and SFG zones of the AR-630 sample leads to the generation of deformation twins and geometrical necessary dislocations (GNDs) in all scales of grain, thus contributing to sustainable high back stress over the whole deformation stage. In contrast, the strain hardening of the AR-740 sample is dominated by the dislocation and twin hardening of FG zones with a homogeneous strain state. More importantly, the exceptional cryogenic toughness can be attributed to the following aspects: i) ductile fracture mode induced by twinning-induced plasticity (TWIP) effect generated by high stacking fault energy (SFE); ii) a more heterogeneous strain partitioning, which can alleviate the strain concentration in the weak FG zones, and also induce more nano-twins in the UFGs and SFGs to impede the crack propagation. The hierarchy modification is of great significance for the practical application of HGS to improve the cryogenic-temperature mechanical performance. Graphical abstract: Image, graphical abstract